Revisiting the role of melatonin in human melanocyte physiology: A skin context perspective. Issue 3 (14th March 2022) - Sevilla, Alec; Chéret, Jérémy; Slominski, Radomir M.; Slominski, Andrzej T.; Paus, Ralf
Abstract: The evolutionarily ancient methoxyindoleamine, melatonin, has long perplexed investigators by its versatility of functions and mechanisms of action, which include the regulation of vertebrate pigmentation. Although first discovered through its potent skin‐lightening effects in amphibians, melatonin's role in human skin and hair follicle pigmentation and its impact on melanocyte physiology remain unclear. Synthesizing our limited current understanding of this role, we specifically examine its impact on melanogenesis, oxidative biology, mitochondrial function, melanocyte senescence, and pigmentation‐related clock gene activity, with emphasis on human skin, yet without ignoring instructive pointers from nonhuman species. Given the strict dependence of melanocyte functions on the epithelial microenvironment, we underscore that melanocyte responses to melatonin are best interrogated in a physiological tissue context. Current evidence suggests that melatonin and some of its metabolites inhibit both, melanogenesis (via reducing tyrosinase activity) and melanocyte proliferation by stimulating melatonin membrane receptors (MT1, MT2). We discuss whether putative melanogenesis‐inhibitory effects of melatonin may occur via activation of Nrf2‐mediated PI3K/AKT signaling, estrogen receptor‐mediated and/or melanocortin‐1 receptor‐ and cAMP‐dependent signaling, and/or via melatonin‐regulated changes in peripheral clock genes that regulate human melanogenesis, namely Bmal1 and Per1 . Melatonin and its metabolites also accumulate in melanocytes where they exert net cyto‐ and senescence‐protective as well as antioxidative effects by operating as free radical scavengers, stimulating the synthesis and activity of ROS scavenging enzymes and other antioxidants, promoting DNA repair, and enhancing mitochondrial function. We argue that it is clinically and biologically important to definitively clarify whether melanocyte cell culture‐based observations translate into melatonin‐induced pigmentary changes in a physiological tissue context, that is, in human epidermis and hair follicles ex vivo, and are confirmed by clinical trial results. After defining major open questions in this field, we close by suggesting how to begin answering them in clinically relevant, currently available preclinical in situ research models.